1997
DOI: 10.1016/s0029-7844(97)00283-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autoantibodies on the Course of Pregnancy and Fetal Growth

Abstract: Antithyroid microsomal antibody and antinuclear antibody are the only autoantibodies that increase the abortion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
4
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 26 publications
3
76
4
6
Order By: Relevance
“…However, the negative results may be skewed by the fact that the analysis was performed only in positively screened women. Nevertheless, some other previous studies also didn't find any link between TPOAb titers and obstetric complications [23,28].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the negative results may be skewed by the fact that the analysis was performed only in positively screened women. Nevertheless, some other previous studies also didn't find any link between TPOAb titers and obstetric complications [23,28].…”
Section: Discussionmentioning
confidence: 70%
“…The rate of PTD varied from 4 to 26.8 % in TPOAb-positive women and 3-8.2 % in TPOAbnegative controls [22,23,24,25]. The causality of this…”
Section: Discussionmentioning
confidence: 92%
“…Negro et al demonstrated that T 4 treatment in women with TAI significantly decreased the number of miscarriages (94,119). In a Japanese study (120) in which seven different types of autoantibodies were evaluated, excluding anticardiolipin, a similar prevalence of prematurity was observed in the control group compared with women with at least one positive antibody. A review (121) indicates that, besides antiphospholipid antibodies, the presence of other autoantibodies is also associated with recurrent pregnancy loss.…”
Section: European Journal Of Endocrinologymentioning
confidence: 91%
“…The studies differed in various aspects. Some had followed a cohort (235)(236)(237)248,250,252,253,(260)(261)(262)(263)(264)(265)(266)(267)(268)(269)(270)(271) (B,A,B,B,B,B,B,A,B-B) and others were "case-controlled" studies (251,254,(272)(273)(274)(275) (C,C,C,C,C).…”
Section: What Is the Role Of Thyroid Autoimmunity In Fertility And Prmentioning
confidence: 99%